Variação temporal da carga de nutrientes e clorofila no Baixo São Francisco para os anos de 2008, 2009 e 2010 - Santos, Rogério da Silva (2020)
The construction of dams for hydroelectric power generation on the São Francisco River formed a cascade of dams and reservoirs along the main axis of the river, modifying the flows and the supply of suspended material in the Sub-medium and Lower SFR. The present work evaluated the load of phosphorus orthophosphate, nitrogen ammonium, nitrite and nitrate in the São Francisco River during the years 2008, 2009 and 2010, measured the concentration of nitrogen and dissolved phosphorus, related the load values with the flow and precipitation, analyzed the chlorophyll concentration and calculated the Trophic State Index to assess the level of eutrophication in the lower São Francisco River AL / SE - Brazil. The studied area is at latitude 10 ° 12 ’S and longitude 36 ° 49’ W, 80 km upstream from the mouth and 100 km downstream from the Xingó Hydroelectric Plant. In this study, Dissolved Inorganic Nitrogen (NID) and Dissolved Inorganic Phosphorus (PID) can be considered low when compared to other tropical rivers. After the completion of the dam cascade and the regulation of river flow after 1995, specific NID and PID loads decreased to levels below tropical rivers that already had lower specific loads. Nitrite and ammonia showed similar behavior, presenting higher loads in the months of higher flow. The greatest straps above the annual nitrate average occurred in the months with the highest flow rates, demonstrating a relationship between increased flow and increased monthly load. For orthophosphate phosphorus there was no standard behavior, occurring above the annual average in years of lower flow rates. The comparison of the yield (yield) of SFR NID and PID with other tropical rivers shows that differences in gradient, size, vegetation cover and engineering works had different effects on specific nutrient loads. The São Francisco River had a yield below other rivers in the world. The values obtained show that the average IET (Trophic State Index) in the three years under study indicates the degree of trophy in the São Francisco River for ultra-oligotrophic, a very low trophic state, which are clean bodies of water, with low productivity, insignificant concentrations of nutrients without prejudice to the use of the waters.